Smart Sensor in Water Flow Monitoring Model using Microcontroller and Raspberry PI - Al-Khowarizmi Al-Khowarizmi; Frainskoy Rio Naibaho (The IJICS (International Journal of Informatics and Computer Science), 2021)
Water is the source of human, animal and plant life which can be said to be living things. However, the need for clean water in the world is increasing along with the growth in the number of living things in the world. The scarcity of clean water is often found due to the wasteful use of water by humans and dirty water due to waste generated by humans. Thus the technology in hardware and software midwives plays a very important role in overcoming water savings for the survival of living things in order to survive. We don't know the use of water that we usually use in a day directly. If we look at the water meter in our house we don't have a display of the cost of water usage and how much water we use in a day. Rapidly developing technology is able to overcome this problem by building a system for calculating the water flow rate and the application to display the cost of using water using a water flow sensor and making a display application that is a user interface so that it will make it easier for humans to run this system and make a smart system model using a method that is used as a user interface. old like the microcontroller and the technology that was developing raspberry pi.